Techniques of reducing papr and ber of ofdm system - Evelyn, Foo Khai Wei (Universiti Malaysia Sarawak (UNIMAS), 2009)
In this 21st century, many wireless applications, such as indoor wideband mobile radio systems, broadband communication wireless internet, and multimedia communications have great demand on a next generation wireless transmission technique that can provide high data transfer rate for better transmission quality. Orthogoanl Frequency Division Multiplexing, OFDM is one of the techniques capable in eliminate problems associated with multipath and frequency selective fading channels efficiently and has the ability to robust against narrowband interference. The disadvantages in OFDM which affects its performance include large Peak-To-Average Power Ratio (PAPR), Phase Noise and Frequency Offset. This project developed a communication system based on OFDM modulation techniques by using SIMULINK tools in MATLAB. Block Coding Schemes has been employed to reduce the PAPR of the OFDM system. The BER performances of the OFDM system are also measured. The Generator Matrix is the most effective techniques of PAPR and BER of the OFDM system.